The future of the nanoparticle. Issue 1 (January 2019) - Unknown
Abstract : Engineered nanoparticles that seem like today's water treatment panacea, could be tomorrow's ecological dynamite. This article plots a roadmap to a future in which we can take advantage of the benefits of nanotechnology in water and mitigate against the drawbacks.